PENGARUH EARNING POWER, LEVERAGE, DAN FREE CASH FLOW TERHADAP MANAJEMEN LABA DENGAN KEPEMILIKAN INSTITUSIONAL - Alya Ramadhani; Nurlaili Nurlaili; Yulistia Devi (Smart Education, 2025)
Abstract: The growing practice of earnings management by businesses, particularly those in the healthcare industry listed on the Indonesia Stock Exchange (IDX) for the 2022–2023 period, is what spurred this study. Financial reports may lose credibility as a result of this technique since the data presented no longer accurately depicts the state of the business. Earning power, leverage, and free cash flow are some of the characteristics that are thought to be the primary causes of earnings management. Nonetheless, institutional ownership is thought to be able to regulate the connection between these elements and earnings management strategies due to its substantial monitoring role. This study uses a quantitative technique and secondary data from the annual reports of 25 companies in the healthcare sector. The analysis techniques used are panel data regression and moderated regression analysis (MRA), both of which are made possible by the EViews 12 program. The results of the study show that free cash flow and earning power considerably deteriorate earnings management, whereas leverage greatly enhances it. Additionally, it has been shown that while institutional ownership can lessen the effect of free cash flow on earnings management, it is unable to lessen the influence of earning power and leverage. This research highlights how crucial institutional ownership is in regulating earnings management techniques, particularly in light of the post-pandemic economic recovery. Keyword: earnings management, earning power, free cash flow, institutional ownership, leverage. Abstrak: Meningkatnya praktik ini didasarkan pada manajemen laba perusahaan, termasuk perusahaan dengan terdaftar pada Bursa Efek Indonesia (BEI) antara tahun 2022 dan 2023. Praktik ini dapat mengurangi kredibilitas laporan keuangan karena informasi yang diberikan tidak mencerminkan keadaan sebenarnya perusahaan. Karena memiliki fungsi pengawasan yang kuat, kepemilikan institusional diperkirakan mampu memoderasi hubungan antara elemen-elemen tersebut dengan praktik manajemen laba. Di sisi lain, beberapa elemen, seperti kekuatan pendapatan, leverage, dan aliran kas bebas, dianggap sebagai pemicu utama munculnya manajemen laba. Pendekatan kuantitatif dipakai pada kajian ini, juga data sekunder dengan digunakan berasal dari laporan tahunan 25 perusahaan dalam bidng perawatan kesehatan. Analisis regresi moderat (MRA) dan regresi data panel dijalankan menggunakan program EViews 12. Perolehan kajian memerlihatkan bahwasanya kepemilikan institusional memoderasi dampak free cash flow pada manajemen laba, tetapi dampak earning power dan leverage sangat negatif. Hasil ini menunjukkan betapa pentingnya kepemilikan institusional dalam mengatur praktik manajemen laba, terutama dalam pemulihan ekonomi setelah pandemi. Kata kunci: earning power, free cash flow, kepemilikan institusional, leverage, manajemen laba.